ERROR ANALYSIS ON TOURISM ARTICLES IN WEBSITE WWW.BATU.EASTJAVA.COM - RIGANTARA, LANANG REKSA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Information about tourism is important, especially for guiding foreigntourists who want to go on vacation. Many media can be the source of information about tourism, one of them is website. In Indonesia, there are some websites which give information about tourism in English, but, still, there are errors appear in it. It is natural because English and Indonesian have different grammatical rules.In this study, the researcher examines (1) the kinds of errors and (2)calculates the frequency of occurrence of each type of error find on tourismarticles in website www.batu.eastjava.com. The researcher uses descriptivequalitative approach and document analysis in order to answer the researchproblems. In this research, the researcher classifies the errors based on Dulay etal’s theory. The data are sixteen tourism articles in website www.batu.eastjava.com. In data collection, the researcher provides the sixteentourism articles in website www.batu.eastjava.com and analyzed them one by one.This study reveals errors that appear in various cases, there are omission,addition, misformation and misordering. Omission is devided into seven, they are omission of pronoun, omission of preposition, omission of be, omission of plural marker, omission of article, omission of noun, and omission of clause marker.The next is addition. Then, misformation is devided into seven, they are misformation of adverb, misformation of be, misformation of conjunction, misformation of singular verb, misformation of preposition, misformation of adjective, and misformation of verb. And for the last is misordering. The total number of errors is 223. The dominant errors that the writer find in the tourism article is omission (OM) with 141 errors (63%), followed by addition (AD) with 18 errors (8%), then misformation (MF) with 57 errors (26%), and the smallest number is misordering (MS) with 7 errors (3%).  The researcher suggests the next researcher who wants to conduct a similarresearch use another theory or other website articles like business, music, etc. Keywords: error analysis, surface strategy taxonomies, kinds of errors.